2023
DOI: 10.1021/acs.bioconjchem.3c00185
|View full text |Cite
|
Sign up to set email alerts
|

Live-Cell Mitochondrial Targeted NIR Fluorescent Covalent Labeling of Specific Proteins Using a Dual Localization Effect

Abstract: Here, our designed water-soluble NIR fluorescent unsymmetrical Cy-5-Mal/TPP+ consists of a lipophilic cationic TPP+ subunit that can selectively target and accumulate in a live-cell inner mitochondrial matrix where a maleimide residue of the probe undergoes faster chemoselective and site-specific covalent attachment with the exposed Cys residue of mitochondrion-specific proteins. On the basis of this dual localization effect, Cy-5-Mal/TPP+ molecules remain for a longer time period even after membrane depolariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The peptide fragment Lys-Leu-Val-Phe-Phe (KLVFF) and asymmetric near-red (NIR) anthocyanin-5 (Cy-5) chromophore can combine to form asymmetric NIR KLVFF/Cy-5 probe. [80] The probe can be used for selectively targeting mitochondria and NIR imaging. The study found that KLVFF/Cy-5 possessed high light stability, high fluorescence lifetime and high fluorescence quantum yield.…”
Section: High Fluorescence Quantum Yieldmentioning
confidence: 99%
“…The peptide fragment Lys-Leu-Val-Phe-Phe (KLVFF) and asymmetric near-red (NIR) anthocyanin-5 (Cy-5) chromophore can combine to form asymmetric NIR KLVFF/Cy-5 probe. [80] The probe can be used for selectively targeting mitochondria and NIR imaging. The study found that KLVFF/Cy-5 possessed high light stability, high fluorescence lifetime and high fluorescence quantum yield.…”
Section: High Fluorescence Quantum Yieldmentioning
confidence: 99%